Peningkatkan Kemampuan Penyelenggaraan Layanan Bimbingan dan Konseling bagi Guru Kelas di Gugus IX Dhandhanggula UPTD Dikpora Jebres Surakarta melalui Supervisi Kelompok - Hartanti, Tri (Universitas Muhammadiyah Surakarta, 2016)
The research is aimed to: 1) describe the implementation of directive supervision to improve the classroom teachers in providing the guidance and counseling; and 2) to improve the classroom teachers ability in providing the the guidance and counseling for the teachers at Gugus IX Dhandhanggula UPTD Dikpora Kecamatan Jebres of Surakarta through the directive suprevision.The research is an action research. The research was done atGugus IX Dhandhanggula UPTD Dikpora Kecamatan Jebres of Surakarta in academic year 2012/2013. The subject of the research were 12 clasroom teachers. The data collecting method were done using interview and observation. The data analysis was done using path model from Kemmis and Taggart.The research concludes that: 1) the directive supervision to improve the classroom teachers ability in providing the the guidance and counseling was done as follows: (a) the supervisor socialize the supervision program to the teachers; (b) the supervisor arranged the supervision schedule; (c) the supervisor provide the supervision materials; (d) the supervisor provide the guidance and counseling simulation; and (e) the supervisor asses the teachersâ ability in providing the guidance and counseling; and 2) The directive supervision is effective in improving the classroom teachers ability in providing the the guidance and counseling. It is demonstrated with the improvement in the teachersâ scores in each cycles.